(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: This study examined the effect of drinking and gargling on thirst perception (TP) in 33 young dehydrated female subjects (18-25yrs), using the visual analogue scale (VAS). Group A subjects drank, while group B gargled the fluid provided - 0.0%, 0.9% and 1.8% NaCl (7.0 ml/kg body weight of fluid). The procedure was alternated two weeks later. All subjects dehydrated for 18 hours prior to the study, and the last 12-hour urine was collected and volume recorded. Subject who provided a 12hr urine volume greater than 400ml was excluded from the study. After recording the baseline TP, and voiding the bladder, drinking/gargling was done within 5 minutes, and the subsequent TPs were recorded at 5 minutes interval for 25 minutes. Blood samples were collected before and at the end of the 30 minutes, when urine volumes were recorded. Drinking (0.0% and 1.8% NaCl) resulted in an initial decrease in thirst perception, which was statistically significant (p<0.05) only up to 10 minutes. Water intake ad libitum (mean ± SEM) at the end of the 30 minutes was statistically significantly lower (p<0.05) only in the group that drank 0.0% NaCl. Gargling on the other hand did not affect TP and water intake throughout the period of study. It can be concluded that drinking, but not gargling reduces thirst perception irrespective of the tonicity of the fluid as earlier reported (Obika et. al., 2009; Salata et. al., 1987). This study suggests that the oropharyngeal receptors for TP are activated by recurrent stimulation by the act of drinking rather than gargling.